Cross-Border Bank Resolution : Recent Developments. (Policy Papers; Policy Paper ;, 2014)
Developing an effective framework for cross-border resolution is a key priority in international regulatory reform. Large bank failures during the global financial crisis brought home the lack of adequate tools for resolving 'too-big-to-fail' institutions. In cross-border cases, misaligned incentives and lack of robust mechanisms for resolution and cross-border cooperation left some country authorities with little choice but to take unilateral actions, which contributed to the high fiscal costs of the crisis and resulted in disorderly resolution in some cases.